Qoheleth : a continental commentary - Lohfink, Norbert; McEvenue, Sean (Minneapolis, MN : Fortress Press, 2003)
"This new addition to the successful Continental Commentary series is a significant and fresh treatment of Qoheleth (or Ecclesiastes). A famed professor presents a startlingly new translation of this often perplexing book of the Old Testament. Lohfink also argues for a rather different interpretation of the book than one finds elsewhere. Rather than reading the book's perspective as depressing, lost, or cynical, he highlights the elements of joy and balance. The volume includes introduction, new translation, commentary, parallel passages, bibliography, and indexes"--Publisher description.
Introduction. Survey of the contents -- History of interpretation -- Era and circumstances of writing -- A model of enculturation -- Linguistic form -- Structure -- The Israelite content -- Authorship -- The book and the canon -- Literary genre -- Qoheleth's philosophy -- The theological challenge of Qoheleth -- Translation. Commentary.
Includes bibliographical references (p. 145-150) and index.
Originally published in German in 1980; with new preface and updated bibliography.
Keywords: Bible. -- Commentaries; Ecclesiastes -- Commentaries; Commentaries